Thermal preferences of two spider species: an orb-web weaver and a synanthropic funnel-web weaver. Issue 1 (1st January 2021) - Napiórkowska, T.; Templin, J.; Grodzicki, P.; Kobak, J.
Abstract: Temperature, an important factor in the ecological niche, determines the individual fitness, distribution and abundance of many spider species. Typically, spiders from different habitats have different thermal preferences, which vary depending on the season, time of day, and reproductive status. Selected temperatures may also depend on thermal acclimation of animals. The study aimed at determining preferred temperatures of females of two spider species, synanthropic Eratigena atrica and garden Araneus diadematus, exposed to low (14°C) and high (23°C) acclimation temperatures. The mean preferred temperature observed in a thermal gradient varied between the species: E. atrica selected 13.7 ± 1.0°C, while A. diadematus selected 22.5 ± 1.5°C, irrespective of the acclimation temperature. Accordingly, thermal niche overlaps between the species were significantly lower than predicted by the random distribution. E. atrica changed their thermal environment on average 12.8 ± 1.9 times during the test, which made them more mobile than A. diadematus, changing their thermal environment 2.7 ± 0.5 times. On the other hand, the thermal niche breadth of A. diadematus acclimated to warm temperature was wider than that of E. atrica . The female behaviour may be related to the selection of optimal conditions with regard to food availability (location for web construction), shelter and/or, in the case of E. atrica, embryonic development.